Dry-method electrode plate for electrolyzing water as well as preparation method and application of dry-method electrode plate
Through the dry electrode process, the dry electrode film is prepared by rolling powder mixture and is combined with the electrode sheet substrate, which solves the high cost and high energy consumption problems caused by solvent use in the wet electrode process, and achieves a more efficient and environmentally friendly electrode preparation.
Patent Information
- Application Number
- CN202411607729.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-12
AI Technical Summary
In the existing electrolytic technology, the wet electrode process requires the use of solvents, which leads to high costs, high energy consumption and uneconomical environmental protection.
The dry electrode process is adopted to prepare the dry electrode film by rolling press of the powder mixture, and the electrode is prepared in combination with the electrode substrate to avoid the solvent use and drying process.
The process flow is simplified, raw material and energy consumption costs are reduced, environmental pollution is reduced, and preparation efficiency and electrode performance are improved.
Smart Images

Figure CN119506931A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water electrolysis, and in particular to a dry electrode sheet and a preparation method thereof. Background Art
[0002] At present, the field of water electrolysis usually adopts solvent-based coating or spraying wet electrode production process, which usually involves mixing substances such as catalysts, conductive agents and polymers in a solution, and then depositing the mixture on the electrode substrate by coating or spraying, and finally forming the electrode through a drying process. This manufacturing method introduces solvents, which increases the cost of solvent use. At the same time, since an additional drying process is required to remove excess solvent, it has high energy consumption and is not environmentally friendly.
[0003] The dry electrode process, on the other hand, directly mixes substances such as catalysts in the form of powders or nanoparticles without solvents, and directly presses the mixture into electrode plates to form electrodes. It can simplify the process flow, avoid tedious steps such as solution preparation, coating and drying, and greatly improve the preparation efficiency. In addition, since a large amount of solvents and energy are not required for solution preparation and drying processes, the dry electrode process has lower energy consumption and less environmental impact. Therefore, the dry electrode process is of great significance in the field of water electrolysis.
[0004] Patent CN 109755473 A discloses a dry method for preparing lithium battery electrodes, which limits the raw materials used in lithium battery electrodes. Patent CN 112420986 B discloses a dry method for preparing positive and negative electrodes of lithium batteries, which reduces the polarization of the battery by adding solid electrolyte powder to the positive and negative electrodes. However, the above processes are mainly used in lithium batteries and do not involve the application of electrolyzed water. Summary of the invention
[0005] The present invention relates to a dry electrode sheet for electrolyzing water and a preparation method thereof, and the technical scheme adopted is:
[0006] A dry electrode sheet for electrolyzing water, characterized in that the electrode sheet at least comprises a dry electrode sheet film prepared by rolling a powder mixture, the powder mixture comprises 80wt%-98wt% of powder active material and 2wt%-20wt% of powder binder, the thickness of the electrode is 20μm-500μm, and the compaction density is 30.0mg / cm 3 -200.0mg / cm 3 .
[0007] In one embodiment, the dry electrode plate membrane for water electrolysis proposed in the present invention can be further composited on one side or both sides of the plate substrate by hot pressing.
[0008] In one embodiment, the present invention provides a method for preparing a dry electrode sheet for electrolysis of water, comprising the following steps:
[0009] (1) Mixing: adding the powdered active substance and the powdered binder into a mixer to obtain a uniformly mixed powdered mixture, wherein the powdered mixture comprises 80 wt% to 98 wt% of the powdered active substance and 2 wt% to 20 wt% of the powdered binder;
[0010] (2) pulverizing: pulverizing the uniformly mixed powder mixture obtained in step (1) by a jet mill to obtain a powder mixture with uniform particle size;
[0011] (3) Molding: Using a twin-screw extruder or an open mill that can continuously provide high shear force, the powder binder in the powder mixture with uniform particle size obtained in step (2) undergoes a fiberization reaction, and the fiberized powder mixture is extruded or rolled to obtain a continuous sheet with a thickness of 200 μm to 1000 μm;
[0012] (4) Rolling: Roll the sheet obtained in step (3) into a 20 μm-500 μm electrode film; the compaction density is 30.0 mg / cm 3 -200.0mg / cm 3 .
[0013] The present invention proposes an implementation scheme of a method for preparing a dry electrode plate for electrolysis of water, further comprising compounding the electrode film produced in step (4) with an electrode substrate through a compounding machine to form a structure of electrode film / electrode substrate or electrode film / electrode substrate / electrode film.
[0014] The present invention proposes an embodiment of a method for preparing a dry electrode plate for electrolysis of water, wherein the powder mixture further contains 80wt%-98wt% of powder active substance, preferably 90wt%-98wt% of powder active substance, and the powder active substance includes at least one metal, metal compound or alloy material selected from iron-based, cobalt-based, nickel-based or copper-based metals.
[0015] The present invention provides an embodiment of a method for preparing a dry electrode plate for electrolyzing water, wherein the powder mixture further comprises 2wt%-20wt% of a powder binder, preferably 2wt%-10wt% of a powder binder, and the powder binder is a mixture of one or more of polyvinylidene fluoride powder, polytetrafluoroethylene powder, acrylic resin powder, polymethacrylic resin powder, and styrene-butadiene rubber powder in any proportion.
[0016] The present invention proposes an implementation scheme of a method for preparing a dry electrode plate for electrolysis of water, wherein the electrode plate substrate includes but is not limited to nickel felt, stainless steel felt, nickel felt, nickel mesh, titanium mesh, foamed nickel, aluminum felt, foamed copper, and polymer film.
[0017] The present invention provides an implementation scheme of a method for preparing a dry electrode plate for water electrolysis, wherein the temperature in the preparation process is controlled below the melting point of the powder binder.
[0018] The electrode film can be directly made into a dry battery electrode, which is independently assembled as a catalyst layer in electrolyzed water; the present invention further includes a dry battery electrode that combines the electrode film and the electrode substrate, which is independently assembled as an electrode or membrane electrode in electrolyzed water. The present invention does not involve solvents, effectively reducing the cost of solvent use and drying links in the preparation process.
[0019] Compared with the wet electrode process, the present invention has the advantage that the electrode preparation process of the present invention does not require the use of solvents, reduces raw material costs and drying costs, shortens electrode preparation time, and avoids solvent contamination problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0021] Figure 1 :A schematic diagram of a method for preparing a dry electrode sheet used in the field of water electrolysis technology;
[0022] Figure 2 : The dry electrode sheet obtained in Example 1 is used in a water electrolysis cell, and the current density curve at a cell voltage of 2V;
[0023] Figure 3 Current density test curves of electrode films with different thicknesses at a cell voltage of 2V;
[0024] Figure 4 Performance comparison of dry electrode and wet electrode under the same test conditions. DETAILED DESCRIPTION
[0025] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0026] The following embodiment provides a dry electrode plate and a preparation method thereof for use in the field of water electrolysis technology, wherein the electrode plate is prepared by compounding an electrode plate film formed by rolling a powder mixture with an electrode plate substrate. The steps include:
[0027] (1) adding powdered active substances and powdered binders into a three-dimensional mixer for mixing so that the various powder mixtures are evenly distributed;
[0028] (2) crushing the uniformly mixed powder mixture obtained in step (1) by a jet mill to obtain a powder mixture with uniform particle size;
[0029] (3) Extruding the powder mixture with uniform particle size obtained in step (2) into 500 sheets through a twin-screw extruder;
[0030] (4) rolling the sheet obtained in step (3) into an electrode film;
[0031] (5) Compounding the electrode film obtained in step (4) with the electrode substrate into a two-in-one structure.
[0032] The powder mixture in step (1) further comprises 80wt%-98wt% of powder active substances, preferably 90wt%-98wt% of powder active substances, wherein the powder active substances include at least one metal, metal compound or alloy material selected from the group consisting of iron-based, cobalt-based, nickel-based or copper-based metals.
[0033] The powder mixture in step (1) further comprises 2wt%-20wt% of a powder binder, preferably 2wt%-10wt% of a powder binder, wherein the powder binder is a mixture of one or more of polyvinylidene fluoride powder, polytetrafluoroethylene powder, acrylic resin powder, polymethacrylic resin powder, and styrene-butadiene rubber powder in any proportion.
[0034] In step (4), the electrode film thickness is 20 μm-500 μm, and the compaction density is 30.0 mg / cm 3 -200.0mg / cm 3 ;
[0035] The electrode substrate in step (5) includes but is not limited to nickel felt, stainless steel felt, nickel felt, nickel mesh, titanium mesh, nickel foam, aluminum felt, copper foam, and polymer film.
[0036] In the above preparation process, the temperature is controlled below the melting point of the powder binder in step (1).
[0037] Example 1
[0038] A dry electrode sheet for use in the field of water electrolysis and a preparation method thereof, the steps are as follows:
[0039] (1) 97 wt% of nano-iron-nickel-cobalt alloy powder (particle size 8-13 μm) and 3 wt% of polytetrafluoroethylene (PTFE) powder binder (particle size 7-9 μm) were added to a three-dimensional mixer, the mixing time was set to 3 hours, the mixing speed was 400 r / min, and the stirring temperature was controlled at 30° C. until a uniform powder mixture was obtained.
[0040] (2) The uniformly mixed powder is crushed by a jet mill, using nitrogen as the working gas, the pressure is set to 0.6 MPa, and the temperature is controlled at 25°C. After crushing, a uniform powder with a particle size of about 2.7-4.2 μm is obtained.
[0041] (3) The crushed powder mixture was extruded through a twin-screw extruder, the extrusion temperature was set at 80°C, the extrusion speed was 30 mm / s, and a sheet with a thickness of 500 μm was obtained, and the fiberization rate reached 86%. The screw speed of the extruder was set at 60 rpm, and the extrusion pressure was maintained at 2 MPa to ensure uniform flow of the material throughout the extrusion process. After extrusion, the sheet was cooled to room temperature.
[0042] (4) The extruded sheet was passed through a calender and rolled at 100°C with a rolling pressure of 20 MPa to a thickness of 200 μm. The final compaction density was 180 mg / cm 3 The roller speed of the roller press is set to 10rpm, and the roller distance is precisely controlled to 0.2mm to ensure uniform compaction and thickness consistency of the sheet. The surface of the sheet after rolling must remain smooth and free of cracks to obtain the anode electrode film.
[0043] The anode electrode film prepared in this embodiment, the anode diffusion layer (nickel felt), PiperION TM A40 anion exchange membrane, platinum black carbon paper cathode (platinum black content 2.0 mg / cm 2 , Fuel cell, 11060028) was assembled into an electrolytic cell, and the electrolyte was 1M KOH. Figure 2 It can be seen that when the electrolytic water tank using the dry electrode sheet is under a cell voltage of 2V, the reaction current density is as high as 1Acm -2 , showing higher activity.
[0044] Example 2
[0045] A dry electrode preparation method for composite nickel foam substrate with electrode films of different thicknesses:
[0046] (1) 90 wt% of iron-nickel alloy powder active material (5.6 μm-6 μm, Sejiaweier) and 10 wt% of PVDF powder (12-18 μm) binder were added into a three-dimensional mixer and mixed for 2 hours at a speed of 1000 r / min and a stirring temperature of 30°C to obtain a uniform powder mixture.
[0047] (2) The mixed powder is crushed by a jet mill, and the particle size distribution after crushing is controlled at 3-8 μm. The crushing time is 2 hours, and finally a uniform powder mixture is obtained. Nitrogen is used as the working gas in the crushing process to prevent oxidation. The pressure of the crushing equipment is set to 0.7 MPa. After crushing, samples are taken for particle size analysis to ensure that the particle size is controlled within the target range.
[0048] (3) The powder mixture was extruded through a twin-screw extruder to form sheets with thicknesses of 100 μm, 200 μm, and 300 μm, respectively. The extrusion temperature was set at 80°C and the extrusion speed was 25 mm / s. During the extrusion process, the screw speed was controlled to be 50 rpm and the extrusion pressure was maintained at 2.5 MPa. The extruded sheet was cooled by a cooling roller to ensure its dimensional stability.
[0049] (4) The electrode films of different thicknesses were rolled into electrode films of 50 μm, 100 μm and 150 μm thicknesses at 100 °C by a calender, and the compaction densities were 150 mg / cm 3 、200mg / cm 3 and 250mg / cm 3 During the rolling process, the roller speed is set to 10rpm, and the roller distance is precisely adjusted to 0.05mm to ensure uniform thickness of the membrane and avoid cracks or other defects to obtain the anode electrode membrane.
[0050] (5) The rolled electrode film is laminated onto the nickel foam substrate by hot pressing. The lamination temperature is set to 120° C., the hot pressing pressure is 3 MPa, and the lamination time is 15 minutes to form a composite structure anode of the electrode film / nickel foam.
[0051] The composite electrode prepared in Example 2 was used as the anode for water electrolysis, and the platinum black carbon cloth electrode (2 mg / cm 2 , Fuel cell, 11060064) as cathode, anion exchange membrane is PiperION TM A40, water electrolysis test in 1M KOH solution. Figure 3 As shown in the figure, under the test condition of constant terminal voltage of 2V, when the electrode film thickness is 150μm, the reaction current density is 1.02Acm -2 When the electrode film thickness is 100 μm, the reaction current density is 1.2 A cm -2Compared with the electrode membrane with a thickness of 150μm, the current density is increased by 17.6%; when the electrode membrane thickness is 50μm, the reaction current density is 2Acm -2 Compared with the electrode membrane with a thickness of 150μm, the current density is increased by 96.1%.
[0052] Comparative Example 1
[0053] Performance comparison with wet electrode:
[0054] (1) The active material of the iron-nickel alloy powder (5.6 μm-6 μm, Sejiaweier) and the binder of the PVDF powder (12-18 μm) were dispersed in an isopropanol solvent, wherein the mass ratio of the iron-nickel alloy powder to the PVDF powder was 9:1, and the mass ratio of the solid to the solvent was set to 1:24. Ultrasonic dispersion was performed for 1 hour using an ultrasonic disperser, with an ultrasonic frequency of 40 kHz and a temperature controlled at 25°C to ensure that the powder was evenly dispersed in the solvent to obtain a uniform electrode slurry.
[0055] (2) The electrode slurry was uniformly deposited onto the nickel foam substrate using an ultrasonic spraying device, with the spraying rate set to 0.5 mL / min and the base plate temperature set to 60°C. The spraying time was adjusted according to the target thickness until a 150 μm catalyst layer was formed. This catalyst layer was combined with the nickel foam substrate to form a composite structure anode.
[0056] (3) The sprayed electrode was placed in a vacuum drying oven and dried at 60° C. for 2 hours to ensure that the solvent was completely volatilized, thereby obtaining a wet electrode with a catalytic layer thickness of 150 μm.
[0057] The prepared wet electrode was used as the anode for water electrolysis. The platinum black carbon cloth electrode (2 mg / cm 2 , Fuel cell, 11060064) as cathode, anion exchange membrane is PiperION TM A40, water electrolysis test in 1M KOH solution. Figure 4 As shown in the figure, under the test condition of constant terminal voltage of 2V, the wet electrode exhibits a current of 0.75A cm -2 In Example 2, the dry electrode with the same thickness achieved a reaction current density of 1.02A cm under the same test conditions. -2 The reaction current density is 2.4 times higher, which improves the performance by 36%.
[0058] Example 3
[0059] (1) 80 wt % of nickel powder (Beijing Hi-Tech New Materials Technology, 8-12 μm) and 20 wt % of polyvinylidene fluoride (PVDF, 15-30 μm) powder binder were added to a three-dimensional mixer for 1 h at a speed of 200 r / min and a stirring temperature of 20° C. until a uniform powder mixture was obtained.
[0060] (2) The uniformly mixed powder is crushed by a jet mill, the crushing pressure is set to 0.2 MPa, the particle size after crushing is 3 μm, and the temperature is controlled at 20° C.
[0061] (3) The extruder was extruded using a twin-screw extruder at a shear rate of 50 rpm and a temperature of 50° C. to obtain a sheet with a thickness of 200 μm.
[0062] (4) The sheet is passed through a roller press at a pressure of 5 MPa and a temperature of 60°C, and the sheet is pressed to a thickness of 20 μm and a compacted density of 30 mg / cm 3 .
[0063] The anode electrode film prepared in this embodiment, the anode diffusion layer (stainless steel felt), PiperION TM A40 anion exchange membrane, platinum black carbon paper cathode (platinum black content 2.0mg / cm 2 , Fuel cell, 11060028) was assembled into an electrolytic cell, and the electrolyte was 1M KOH. At 2V cell pressure, the reaction current density was 0.54A cm -2 .
[0064] Example 4
[0065] (1) 89 wt % of nickel-iron alloy powder (10-15 μm) and 11 wt % of PTFE powder binder (20-25 μm) were added to a three-dimensional mixer, mixed for 3 hours, rotated at 500 r / min, and stirred at 50° C. to obtain a uniform powder mixture.
[0066] (2) The powder was crushed using a jet mill, the crushing pressure was set to 0.5 MPa, the particle size after crushing was 5 μm, and the temperature was controlled at 40°C.
[0067] (3) The product was processed using a twin-screw extruder at a shear rate of 100 rpm and a temperature of 100° C. to form a sheet of 500 μm.
[0068] (4) The sheet is passed through a roller press at a pressure of 25 MPa and a temperature of 80°C, and the sheet is rolled to a thickness of 250 μm and a compacted density of 115 mg / cm 3 .
[0069] The electrolysis test was carried out in 1M KOH solution. The obtained electrode and stainless steel felt were combined as the anode. The Pt / C electrode (20% Pt on Vulcan XC-72R, Pt loading of 1 mg cm -2 ) as cathode, PiperION TM A40 anion exchange membrane was used as the electrolyte membrane. The cell temperature was 50°C and the voltage was set to 2V. The current density reached 0.77A / cm 2 .
[0070] Example 5
[0071] (1) 98 wt% of nickel-cobalt alloy powder (15-18 μm) and 2 wt% of PVDF powder binder (18-20 μm) were added to a three-dimensional mixer for 5 hours at a rotation speed of 1000 r / min and a stirring temperature of 80° C. to obtain a uniformly mixed powder mixture.
[0072] (2) The powder was crushed by a jet mill, the crushing pressure was set to 0.8 MPa, the particle size after crushing was 10 μm, and the temperature was controlled at 60°C.
[0073] (3) A twin-screw extruder was used for high shear rate processing at a shear rate of 200 rpm and a temperature of 150° C. to form a sheet of 1000 μm.
[0074] (4) The sheet is passed through a roller press at a pressure of 50 MPa and a temperature of 120°C, and the sheet is rolled to a thickness of 500 μm and a compacted density of 200 mg / cm 3 .
[0075] The electrolysis test was carried out in 1M KOH solution. The obtained electrode and stainless steel felt were combined as the anode. The Pt / C electrode (20% Pt on Vulcan XC-72R, Pt loading of 1 mg cm -2 ) as cathode, PiperION TM A40 anion exchange membrane was used as the electrolyte membrane. The cell temperature was 50°C and the voltage was set to 2V. The current density reached 1.05A / cm 2 .
Claims
1. A dry electrode sheet for electrolysis of water, characterized in that: The electrode plate at least includes a dry electrode film prepared by rolling a powder mixture, and the powder mixture includes 80wt%-98wt% (preferably 90wt%-98wt%, more preferably 94wt%-97wt%) powder active material and 2wt%-20wt% (preferably 2wt%-10wt%, more preferably 3wt%-6wt%) powder binder.
2. The dry electrode sheet for water electrolysis according to claim 1, characterized in that: The electrode plate film can be further composited to one or both sides of the plate substrate by hot pressing; the plate substrate includes but is not limited to one or more of nickel felt, stainless steel felt, nickel felt, nickel mesh, titanium mesh, foamed nickel, aluminum felt, foamed copper, and polymer film.
3. The dry electrode sheet for water electrolysis according to claim 1, characterized in that: The powder active material includes at least one metal, metal compound or one or more metal alloy materials containing at least one of iron-based, cobalt-based, nickel-based or copper-based metals, preferably including monovalent active powders: iron nanopowder, nickel nanopowder, cobalt nanopowder, Co3O4, Ni3N nanopowder, single metal (oxy) hydroxide (MO x H y , where M is one or more of Fe, Co, Ni or Mn), binary active powders: nickel-iron nanopowder, NiMo, nickel-iron (oxide or) hydroxide (wherein the molar mass ratio of Fe is 15-50%), LaNiO3, CoCu oxide (Cu 0.7 Co 2.3 O4、Cu 0.5 Co 2.5 O4), CoFeO x and one or more of the multi-element alloy NiCoMo.
4. The dry electrode sheet for water electrolysis according to claim 1, characterized in that: The powder binder is a mixture of one or more of polyvinylidene fluoride powder (PVDF), polytetrafluoroethylene powder (PTFE), acrylic resin powder, polymethacrylic resin powder, and styrene-butadiene rubber powder in any proportion.
5. The dry electrode sheet for water electrolysis according to any one of claims 1 to 4, characterized in that: The thickness of the electrode is 20 μm-500 μm, preferably 20 μm-150 μm, more preferably 20 μm-100 μm; the compaction density is 30.0 mg / cm 3 -200.0mg / cm 3 , preferably 50.0 mg / cm 3 -120.0mg / cm 3 , more preferably 60.0 mg / cm 3 -110.0mg / cm 3 .
6. A method for preparing a dry electrode sheet for water electrolysis according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Mixing: Add powdered active material (particle size 2-100 μm) and powdered binder (particle size 3-15 μm) into a three-dimensional mixer, mix for 1-5 hours, mix at a speed of 200-1000 r / min, and control the temperature at 20° C.-80° C. to obtain a uniform powder mixture; (2) Crushing: The mixture obtained in the previous step is crushed by a jet mill, the crushing pressure is controlled at 0.2-0.8 MPa, the temperature is controlled at 20°C-60°C, and the particle size distribution of the powder after crushing is controlled at 3 μm-10 μm; the working gas of the jet mill should be an inert atmosphere gas (such as one or more of nitrogen and argon) to prevent oxidation of the powder; (3) Molding: The crushed powder mixture is processed by a twin-screw extruder or an open mill under high shear force, with the shear rate controlled at 50-200 rpm and the temperature controlled at 50°C-150°C, so that the powder binder undergoes a fiberization reaction, with the fiberization rate reaching more than 80%, and a sheet with a thickness of 200 μm-1000 μm is obtained by extrusion or rolling; (4) Rolling: The formed sheet is rolled by a roller press, the rolling pressure is controlled at 5MPa-50MPa, the temperature is controlled at 60℃-120℃, and finally the electrode film with a thickness of 20μm-500μm is obtained by rolling, and the compaction density is 30mg / cm 3 -200 mg / cm 3 .
7. The preparation method according to claim 6, characterized in that: The method comprises the steps of laminating the electrode film produced in step (4) on one or both sides of the electrode substrate through a hot pressing laminating machine, wherein the laminating temperature is 100° C.-180° C., the pressure is controlled at 2 MPa-10 MPa, and the laminating time is 10-60 minutes to form a multilayer structure of electrode film / substrate or electrode film / substrate / electrode film.
8. Use of the electrode sheet according to any one of claims 1 to 5 as an anode in electrolysis of water.
Citation Information
Patent Citations
Dry process preparation method of lithium battery electrode
CN109755473A
A dry method for preparing positive and negative electrodes for lithium batteries
CN112420986B
Graphene-based dry battery pole piece, battery and manufacturing method thereof
CN113937289A
Method for preparing electrode membrane of lithium ion battery by dry method
CN115579458A